Reassessing the (In)visibility of Pluricultural Competence in BIPA Assessment: A Critical Discourse Analysis of Basa-Basi Representation in Government-Issued Textbooks - Sry Aji Prabowo Mukti,; Asteria, Prima Vidya; Sodiq, Syamsul (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Pluricultural competence is a critical component in teaching Indonesian as a Foreign Language (BIPA), particularly within the context of intercultural communication, as reflected in the practice of basa-basi (Indonesian small talk). However, the representation of this competence in formal BIPA assessment has received limited critical attention. This study aims to evaluate the visibility of pluricultural competence through the representation of basa-basi in assessment tasks found in government-issued BIPA textbooks. Employing a descriptive qualitative approach and Fairclough’s model of Critical Discourse Analysis (CDA), the study analyzes seven official BIPA textbooks from Levels 1 and 2, with a focus on assessment sections. The findings reveal that the representation of basa-basi remains limited and fails to capture the complexity of Indonesian sociocultural interaction. Assessment items tend to prioritize structural aspects of language while overlooking pragmatic and cultural dimensions. The study concludes that insufficient attention to pluricultural competence in assessment may hinder BIPA learners from achieving full communicative competence. It recommends the explicit integration of basa-basi elements and pragmatic evaluation criteria in BIPA assessments as a step toward strengthening a culturally responsive language teaching approach.